A meta-analysis of the clinicopathological significance of the lncRNA MALAT1 in human gastric cancer - Bai, Shaoxiong; Guo, Jiansheng; Zhang, Haofan (Frontiers in Oncology, 2024)
Background: Dysregulation of the long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been linked to some oncogenic pathways that induce cancer initiation and progression. This meta-analysis was conducted to specifically summarize the most recent research on MALAT1 function in human gastric cancer (GC).The eligible studies were first identified by searching HowNet, Web of Science, PubMed, The Cochrane Library, Embase, and Nature databases for studies published as of April 1, 2023. The meta-analysis included 14 studies assessing MALAT1 expression and presenting clinical parameters and survival outcomes.The results illustrated that high MALAT1 expression is predictive of lymph node metastasis (pooled odds ratio [OR] = 2.99, 95% confidence interval [CI] = 1.97-4.54, P < 0.001) and distant metastasis in GC (OR = 3.11, 95% CI = 1.68-5.75, P < 0.001). In addition, MALAT1 was associated with GC tumor invasion (T3/T4 vs. T1/T2: OR = 2.90, 95% CI = 1.90-4.41, P <0.001) and TNM stage (III/IV vs I/II: OR = 2.93, 95% CI: 1.80-4.77, P <0.001). Additionally, higher MALAT-1 expression predicted poorer overall survival in patients with GC (hazard ratio = 1.64, 95% CI = 1.20-2.09, P < 0.001).The current findings suggest that the high MALAT1 expression is an adverse biomarker for prognostic outcomes, lymph node metastasis, TNM stage, and distant metastasis in GC and MALAT1 could be a prognostic biomarker for GC.